Diagnosis Molekuler Toxoplasma gondii Berdasar Gen Stage Spesifik Takizoit dan Bradizoit pada Ayam Kampung (MOLECULAR DIAGNOSIS OF TOXOPLASMA GONDII BASED ON THE TACHYZOITE AND BRADYZOITE STAGE SPECIFIC GENES IN FREE-RANGE CHICKEN) - Apsari, Ida Ayu Pasti; Artama, Wayan Tunas; ., Sumartono; Damriyasa, I Made (Jurnal Veteriner, 2012)
The aims of this study was to determine the presence of Toxoplasma gondii in free-rangechicken using Polymerase Chain Reaction (PCR) method based on the tachyzoite and bradyzoitestage specific genes. SAG1 and BAG1 are the tachyzoite and bradyzoite stage-specific gene respectively.The primers for SAG1 and BAG1 were designed using Web-base Program Primer 3. Genomic DNAfrom free-range chicken heart and brain was isolated using Pure-Link Genomic Isolation Kit.DNA amplification by PCR using primers for SAG1 and BAG1 genes was used for diagnosis ofT.gondii. The results showed that the DNA amplification using primers for SAG1 and BAG1 geneswas successfully applied to determine of Toxoplasma gondii in free-range chicken.
Keywords: Toxoplasma gondii, SAG1 dan BAG1, Tachyzoite, Bradyzoite, free-range chicken